SSKJ - Perdih, Andrej; Snoj, Marko (Slavia Centralis, 2020)
SSKJ2The second edition of The Dictionary of Standard Slovenian Language (SSKJ) was published in autumn 2014 (frst edition 1970–1991). Its aim is to bridge the content and time gap that arose between the frst edition of SSKJ and the new dictionary of standard Slovenian language yet to be compiled. The article explains the circumstances surrounding the compilation of the second edition of SSKJ and describes innovations in the dictionary content and language description.
Keywords: lexicography; dictionary; Slovenian language; Slovene language; standard language